Parole Revocation in Ohio - Tuma, Robert L. (1962)
Can the Pardon and Parole Commission declare a paroled convict to be a parole violator before the expiration of the maximum period of his sentence without notice or hearing, according to t!he laws of Ohio and the Federal Constitution? Also, is such action by the Commission reviewable by habeas corpus proceedings, even though such convict is returned to an institution because of such action